Law on safety and health in Malaysia - Soehod, Khairiah; Kunju Pillai Laxman, Lekha (Universiti Teknologi Malaysia, 2003)
In today world, rapid economic development has not only led to significant improvements in incomes and the quality of life, but also resulted in great increases in the number of people killed and injured at work. For decades, industries have embraced many systems to minimise workplace accidents and incidents, yet despite the best intention, there has been little reduction in the rate at which people are killed or injured at work. Similar scenario prevails in Malaysia, when statistics from the Social Security Organisation reports indicated that although the number of occupational accidents has reduced gradually, workers especially those in the manufacturing sector still suffer a high level of occupational accidents almost every year. To overcome this problem, the government has come out with a legislative framework to deal with this situation. This study therefore has the purpose of examining safety related matters at work, strictly from the legal point of view. Its objectives are to review the historical background of the implementation of the laws related to safety and health at work; to identify the relevant legislations; and to analyse the extent of the employers’ duties and liabilities related to safety at work under the common law. Qualitative method prone to the legal style of doing research was employed to achieve all the objectives. Hence the data referred in this study consist of all secondary data found in the legislations, legal journals, thesis and law publications. It was found in this study that as a result of several weaknesses in the previous legislations namely the Machinery Ordinance 1953 and Factories and Machineries Act 1967, Occupational Safety and Health Act (OSHA) was enforced in 1994. It provides general guidelines on how to create a safe environment at work. Subsequently many regulations, guidelines and codes of practice which provided more detailed provisions were introduced under OSHA 1994. The results also showed that besides the statutory obligations, employers also have a duty, under the common law, to provide a safe system of work to their workers, failing which an action of negligence could be taken against them in court.